Studentsâ€™ Perceptions towards The Utilization Of â€œWhatsappâ€ for Vocabulary Teaching and Learning - Anita Wijayanti; Yohanes Bambang Gunawan (Universitas Ahmad Dahlan, 2018)
Society has enjoyed the ease of communication afforded by â€œWhatsappâ€, a popular freeware and cross-platform communication application. â€œWhatsappâ€â€™s popularity has invited educators to experiment with it in various ways to shore up education. This study was conducted to describe studentsâ€™ perceptions on the use of â€œWhatsappâ€ for teaching and learning vocabulary. A vocabulary virtual class in the form of a â€œWhatsappâ€ group where students needed to enroll was created for that purpose. This virtual class exempted the students from physically attending the physical class as it enabled students to remotely attend the class. Teaching and learning methods of vocabulary in the virtual class included using pictures, translation, and sentence construction. At the end of the class, the students were to inform the researchers about their perceptions of the virtual class. This study used a descriptive qualitative method. Data was collected through a paper-based questionnaire, which was distributed to all students in a face-to-face class, a session taking place two days prior to the research. The virtual vocabulary class that the researchers administered overall received positive feedbacks from the learners. However, teaching and learning vocabulary using â€œWhatsappâ€ also had its own drawback.